Programa de orientación académica en la retención estudiantil en educación superior universitaria con estudiantes de Ciencias Sociales de la Facultad de Ciencias de la Educación y Humanidades de la Universidad Nacional de la Amazonía Peruana 2024 - Pérez Cavaillier, Sandra del Rocio (2025)
The objective was: To evaluate the effectiveness of the Academic Orientation Program in Student Retention in university higher education with students of Social Sciences of the FCEH - UNAP 2024. The study was applied quantitatively, evaluative type, taking into account the temporality, the respective controls were made: before and after, so the design is quasi experimental because the program was the V.I. which was manipulated to see its effect on the V.D., by means of the pre-test and post-test. The total population consisted of 169 students of CC.SS. enrolled during the 2024 - I semester. The unit of study was extracted in a stratified way because we worked with 59 students. The sample selection was intentional non probabilistic. When performing the descriptive analysis. Before the Academic Orientation in Student Retention 42 (85.7%) responded low, 4 (8.2%) regular and 3 (6.1%) high. After the Academic Orientation in Student Retention 2 (4.1%) responded low, 31 (63.3%) responded regular and 16 (32.7%) responded high. The inferential result, we examined the bilateral significance values of student retention before and after applying the academic orientation. The value was found to be less than 0.05, implying that these distributions do not conform to a normal distribution. Thus, the hypothesis for the hypothesis test for paired or related samples of Wilcoxon signed ranks with sign of Wilcoxon was established to contrast the hypothesis of the study. A Significance level ∞ = Alpha = 0.05 = 5% is achieved. The test statistic is Z standardized to compare linked or paired samples, concluding that the research hypothesis is confirmed at a 95% confidence level. Education Program Implementation: Academic Orientation significantly increases Student Retention in higher university education with students of CC.SS. levels of the FCEH - UNAP 2024.